Religious Thought In Indonesia An Overview - Abdul Muis Naharong (Al-Jami'ah: Journal of Islamic Studies, 1991)
Indonesians, like other people in different parts of the world, are religious people. Different religions and beliefs, whether revealed or nonrevealed, have been embraced and practised with full conviction from time immemorial. This is because, on the one hand, being religious is a particular characteristic of man and, on the other hand, man needs religion. Men live in this world in uncertainty and dependency. This is true not only of primitive and developing societies, but of developed societies as well. In addition, there always emerge problems of destiny, suffering, and death.This fact is further aggravated by the fact that the discrepancy between expectation and actual happenings in society is quite significant It is too frequent that not good but bad men succeed. In this situation, religion is considered a way of making sense of the world which is increasingly difficult to make sense of. With religion men can patiently bear suffering and misfortune; with religion men can legitimate the good fortunes they have. Indeed, "religion has been the historically most widespread and effective instrumentality of legitimation (because) ... it relates the precarious reality constructions of empirical societies with ultimate reality,"1 With religion men can resolutely accept their failure; and with religion men can enjoy their victories the way they should. In sum, religion is able to create power in men. Men who have just communicated with God will feel stronger both in bearing suffering and in conquering it in other words, religion is a means of coping with the world. The importance of religion has officially been recognized by the Indonesian Government since the proclamation of the independence of the Republic of Indonesia as shown in the first principle of Pancasila (Five Principles)2, the national ideology. This paper will discuss the Indonesian Government's view on religion, the general views of Muslims on religion and politics, and the Qur'ān's view on religion.